2004
DOI: 10.1074/jbc.m314043200
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomes Begin Ornithine Decarboxylase Digestion at the C Terminus

Abstract: Proteasomes denature folded protein substrates and thread them through a narrow pore that leads to the sequestered sites of proteolysis. Whether a protein substrate initiates insertion from its N or C terminus or in a random orientation has not been determined for any natural substrate. We used the labile enzyme ornithine decarboxylase (ODC), which is recognized by the proteasome via a 37-residue C-terminal tag, to answer this question. Three independent approaches were used to assess orientation as follows. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 41 publications
(57 reference statements)
3
45
0
2
Order By: Relevance
“…Is that also true of eukaryotic proteasomes? Studies from our laboratory (5,6) and by others (7)(8)(9)(10) are consistent with this conclusion, but studies using purified proteasomes and substrates of well-defined structure have been limited and have not determined the kinetic parameters associated with proteasome action.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Is that also true of eukaryotic proteasomes? Studies from our laboratory (5,6) and by others (7)(8)(9)(10) are consistent with this conclusion, but studies using purified proteasomes and substrates of well-defined structure have been limited and have not determined the kinetic parameters associated with proteasome action.…”
supporting
confidence: 71%
“…Vertebrate forms of ODC have a small conserved degradation tag (22) (37 amino acids in mouse and human) at its C terminus (cODC). Degradation is strictly unidirectional and begins at the tag (5). Fusing this tag to other proteins promotes their rapid turnover by the eukaryotic proteasome (17), including those of mammals, plants, and fungi.…”
Section: Design and Structure Of Substrates Used In These Studies-mentioning
confidence: 99%
“…Even modest reductions in mammalian ODC activity can lead to marked resistance to tumor development (1,2). ODC is turned over rapidly, and this, in part, is because of it being targeted to the 26S proteasome without ubiquitination by the protein antizyme, its key regulator (3,4). Antizyme itself is negatively regulated by antizyme inhibitor, a homolog of ODC with a higher affinity for antizyme that has lost the ability to decarboxylate ornithine (5).…”
mentioning
confidence: 99%
“…Antizyme increases the degradation of ODC by enhancing its interaction with the proteasome but does not increase the rate of proteasomal processing. It was also shown that proteasomes actually start degradation of ODC at the COOH terminus (24). Therefore, rapid degradation of mammalian ODC requires a degradation domain that contains a PEST motif located at the COOH terminus of the protein.…”
mentioning
confidence: 99%